An Error Analysis On Recount Text Written By Students Of Accounting Education: A Case Study On English Tutorial Program (ETP) At Muhammadiyah University Of Surakarta - Buana, Mega Bela; , Prof. Dr. Endang Fauziati, M.Hum (2017)
This study found in recount text written by the students of Accounting Education on English Tutorial Program (ETP) at Muhammadiyah University of Surakarta is aimed to identify the types of morphological, syntactical and discourse errors. The type of this research was qualitative research. The method of collecting data was document analysis. There were 295 data containing errors. The current study adopted error analysis theory of linguistic category and surface strategy taxonomy adopted by James (2013) in Fauziati (2016) for analyzes the data. The steps for analyzing data was classified into error types, describing the frequency of error, describing the dominant type of error, analysis of the sources of error and describing the purpose remedial teaching. The result of the research showed the morphological errors was 22, 72% including, misformation of word in similar meaning, misordering of spelling and blend of Indonesian word. Syntactical error was 69, 14%, which included verb (addition of verb, omission of verb, misuses of verb in past tense, addition of to in verb of present tense), noun (omission of {-s} plural marker), BE (omission of be as predicate, misuses of be as predicate), article (omission of article, addition of article), preposition (addition of preposition, omission of preposition). Discourse error was 8, 14%, which included generic structure, reference, and conjunction. The dominant type of error was misordering of spelling and misuses of verb in past tense.